New glass architecture - Richards, Brent; Gilbert, Dennis (London : Laurence King, 2006)
Much of modern architecture has been conceived using glass to create minimal structures. This book begins with an introduction that traces the history of glass in architecture and also describes the developments in glass technology. It also features specially commissioned photographs by the renowned architectural photographer, Dennis Gilbert.
Includes bibliographical references and index.
Keywords: Glass construction; Architecture, Modern -- 20th century; Architecture, Modern -- 21st century